EFEKTIFITAS TERAPI KOMPRES HANGAT DAN MASSAGE EFFLEURAGE TERHADAP PENGURANGAN RASA NYERI PERSALINAN KALA I FASE AKTIF - Ridesman; Mediyana; Pasaribu, Riska Susanti; Tarigan, Citra Kartika; Sinaga, Asnita (Midwifery And Complementary Care, 2022)
Background: Labor is the process of delivering the fetus that occurs during a full-term pregnancy (37–42 weeks), with spontaneous birth in a cephalic (head-first) presentation, typically lasting within 18 hours and without complications for either the mother or baby. Labor can cause trauma for the mother due to the pain experienced. Some mothers may even develop psychological trauma, making them afraid to become pregnant and give birth again due to fear of experiencing the same pain. Therefore, reducing labor pain can help mothers go through the delivery process more comfortably. Objective: The purpose of this study is to gain deeper understanding and knowledge about the effectiveness of warm compress therapy and effleurage massage in reducing labor pain during the active phase of the first stage of labor. Method:This research is a quasi-experimental study using a design in which subjects in the experimental and control groups are not randomly selected. The approach used is a one-group post-test-only design. Results: The Wilcoxon test results showed a Z count of -5.069 and a Z table value of 1.69 at a 5% significance level. Since Z count > Z table and the p-value was 0.000 (p < 0.05), it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that there is a significant effect of warm compress and effleurage massage on reducing labor pain during the active phase of the first stage of labor. Conclusion: The application of warm compress therapy and effleurage massage can reduce labor pain during the active phase of the first stage of labor.